Engulf and digest – TRPM7 as key regulator of macrophage phagosome maturation. (September 2022) - Hoeger, Birgit; Zierler, Susanna
Highlights: Commentary on Schappe M.S. et al., Efferocytosis requires periphagosomal Ca 2+ -signaling and TRPM7-mediated electrical activity, Nature Communications, 2022, 13. Abstract: Localized intracellular calcium fluxes are indispensable for immunologically directed Fc receptor-mediated cellular phagocytosis. A similar dependency on calcium signals has been speculated to occur in efferocytosis, the clearance of non-opsonized apoptotic cell bodies by macrophages. In a recent study published in Nature Communications, Schappe et al . describe the TRPM7 ion channel as mediator of peri‑phagosomal calcium currents, ensuring maturation of the acidifying phagosome. The authors identified a fundamental calcium signaling module provided by TRPM7, which is necessary for clearance of apoptotic cells. This finding updates our current molecular understanding of calcium dynamics, tissue maintenance and immunological clean-up. Graphical abstract: Image, graphical abstract